(untitled) (Cultura Económica, 2019)
In the present study, the authors analyze the HDI of the United Nations Human Development Program. They intend to show that there are underlying technical and practical assumptions. Not all of them, however, are sufficiently explained or argued. First, Adrogué and Crespo discuss why they consider it as a relevant case of study. Then, the history and the description of the HDI are provided. Thirdly, the difficulties of the index numbers and specifically of the HDI, are explained. Next, the underlying practical assumptions are shown. Finally the authors present their main conclusions and some suggestions about how they believe the index can be improved